Exploring the accessible conformations of N-terminal acetylated α-synuclein - Moriarty, Gina M. (2013)
Alpha synuclein (αsyn) fibrils are found in the Lewy Bodies of patients with Parkinson’s disease (PD). The aggregation of the αsyn monomer to soluble oligomers and insoluble fibril aggregates is believed to be one of the causes of PD. Recently, the view of the native state of αsyn as a monomeric ensemble was challenged by a report suggesting that αsyn exists in its native state as a helical tetramer. This review reports on our current understanding of αsyn within the context of these recent developments and describes the work performed by a number of groups to address the monomer/tetramer debate. A number of in depth studies have subsequently shown that both non-acetylated and acetylated αsyn purified under mild conditions are primarily monomer. A description of the accessible states of acetylated αsyn monomer and the ability of αsyn to self-associate is explored.